MODEL DAN IMPLEMENTASI KEBIJAKAN PENDIDIKAN DI KABUPATEN TAPANULI TENGAH - Sipahutar, Marnita (Tarbiyah : Jurnal Pendidikan Agama Islam, 2024)
Education policy is a collection of rules, vision and mission, achievements to be implemented in order to achieve better education. The education policy prepared in the Restra of the Tapanuli district education office is currently providing achievements that will be implemented, namely implementing 9 years of compulsory education and initiating 12 years of compulsory education, improving the quality of education personnel by increasing teacher qualifications, increasing the competence and professionalism of education personnel, increasing access. equitable education services, Implementing and developing national and local curricula in the learning process at school. Rehabilitation, maintenance and procurement of educational facilities and infrastructure. Improving student achievement with character education. Encourage educational institutions to create a more competitive teaching and learning climate based on academic and regional potential. Introducing the values ​​and cultural diversity found in Central Tapanuli Regency in basic education units. Manage and develop cultural values ​​and cultural diversity. The methodology of this research is library research (Library Research), identifying research objectives to understand education policy in depth. The results of this research are that the policies found in Tapanuli Regency are being prepared in the Restra of the Central Tapanuli Regency education office. Education in Central Tapanuli has been going well and has developed rapidly, and has even given birth to regeneration that serves the country. However, in plain view, the problem of education in Central Tapanuli Regency is that the education office has a policy of 9 years of compulsory education and pioneered 12 years of compulsory education, this is still far from being achieved.